1978
DOI: 10.1159/000155836
|View full text |Cite
|
Sign up to set email alerts
|

Postreproductive Survival and Behavior in a Free-Ranging Female Mangabey

Abstract: The survival and behavior of a postreproductive free-ranging female Cercocebus albigena is documented; her patterns of grooming, aggression, and other social and spatial relationships with members of her group are described and compared with those of other, cycling, females. The phenomenon of female postreproductive survival in free-ranging nonhuman primates is briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Reproductive cessation in our study species was previously reported by Waser (1978). Reproductive aging of females is a conspicuous phenomenon in humans, but is not ubiquitous among other animals (Jones et al 2014;Roach and Carey 2014).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Reproductive cessation in our study species was previously reported by Waser (1978). Reproductive aging of females is a conspicuous phenomenon in humans, but is not ubiquitous among other animals (Jones et al 2014;Roach and Carey 2014).…”
Section: Discussionsupporting
confidence: 70%
“…Females are born with a set number of oocytes, and as females cycle, the pool of available oocytes diminishes and females may enter a postreproductive phase near the end of their life, i.e., menopause (Atsalis and Videan 2009;Bell and Koufopanou 1986;Pavelka and Fedigan 2012;Perheentupa and Huhtaniemi 2009;Waser 1978). The number of oocytes present at birth may depend on the nutrition of the mother before the daughter's birth, whereas the depletion rate of oocytes may depend on the rate of cycling and the frequency of pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have proposed that aged nonhuman primates can provide valuable insights into the clinical symptoms of menopause, a particularly distinctive phase of reproductive aging in human females, in addition to answers concerning the evolutionary significance of the phenomenon (Archer, 2004;Bellino, 2000;Gould et al, 1981;Graham, 1981;Kaplan, 2004;Schramm et al, 2002). To date, related research has focused primarily on macaques (Gilardi et al, 1997;Graham et al, 1979;Johnson and Kapsalis, 1998;Pavelka and Fedigan, 1999;Schramm et al, 2002;Shideler et al, 2001;Small, 1984;Takahata et al, 1995;Walker, 1995), with few data from other monkey species (Borries et al, 1991;Dolhinow et al, 1979;Harley, 1990;Sommer et al, 1992;Strum and Western, 1982;Tardif and Ziegler, 1992;Waser, 1978). Surprisingly, primatologists have investigated ape species markedly less well, though long lifespans, large body sizes, slow life history traits, and close taxonomic ties with humans may make them more suitable paradigms for research on reproductive aging in humans.…”
Section: Introductionmentioning
confidence: 99%
“…1987; Kaplan, 1997) vs. those claims for the existence of menopause in nonhuman primate species (e.g., Hodgen et al, 1977;Waser, 1978;Graham et al, 1979;Hrdy, 1981;Nishida et al, 1990) have led to further studies that seek to clarify the existence and the extent of a postreproductive life in various primates. Many of these more recent studies contribute further competing claims for (e.g., Paul et al, 1993) and against (e.g., Johnson and Kapsalis, 1998) the existence of an adaptive termination of reproduction in nonhuman primates.…”
mentioning
confidence: 99%